La mer de Goldthwait au Québec - Dionne, Jean-Claude (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
The Goldthwait Sea is defined as the late- and post-Glacial marine invasion in the St. Lawrence Estuary and Gulf east of Québec City. In Québec, this sea has submerged an area of about 25 000 km2. The largest areas submerged are the north shore of the St. Lawrence between Les Escoumins and Blanc-Sablon, the south shore between Levis and Tourelles, and the Anticosti Island. The upper limit of the Goldthwait Sea varies from place to place. The Goldthwait Sea began 14 000 years ago and land emergence is still in progress, since the pre-Wisconsin marine level has not been recovered yet. For a better chronology, this long interval needs to be subdivided. Three main periods have been recognized: Goldthwaitian I, II and III. However, a geographical subdivision is also needed. Numerous shorelines were observed at various elevations throughout the area formely submerged by the Goldthwait Sea. However, only a few shorelines are well developed and extensive, and correlations between former shorelines are difficult to establish. Only three levels are widespead and common to the Estuary and parts of the Gulf. The isostatic recovery has been rapid during the first three thousand years after déglaciation of the area: about 75%.